2014
DOI: 10.1111/bph.12633
|View full text |Cite
|
Sign up to set email alerts
|

The μ‐opioid receptor: an electrophysiologist's perspective from the sharp end

Abstract: Morphine, the prototypical opioid analgesic drug, produces its behavioural effects primarily through activation of μ-opioid receptors expressed in neurones of the central and peripheral nervous systems. This perspective provides a historical view of how, over the past 40 years, the use of electrophysiological recording techniques has helped to reveal the molecular mechanisms by which acute and chronic activation of μ-opioid receptors by morphine and other opioid drugs modify neuronal function. ]-enkephalin; GI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…Among the previous studies, mechanisms of morphine tolerance are complex and involve many factors, such as ion channels, receptors, cells, and neural networks [13]. For a long time, extensive studies suggested that neurons participate in the development of morphine tolerance [3, 4].…”
Section: Introductionmentioning
confidence: 99%
“…Among the previous studies, mechanisms of morphine tolerance are complex and involve many factors, such as ion channels, receptors, cells, and neural networks [13]. For a long time, extensive studies suggested that neurons participate in the development of morphine tolerance [3, 4].…”
Section: Introductionmentioning
confidence: 99%
“…More particularly, the exact cellular and synaptic mechanisms of µ-opioidergic modulation in this dMT-amygdala circuit remain unresolved. At the cellular level, ligand-binding to MORs activates G-protein-coupled inwardly rectifying potassium channels (GIRKs) leading to membrane hyperpolarization 19,20 . It has been proven that neurons in the dMT are inhibited by MOR signaling via this mechanism 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Stefan Schulz's group review their pioneering work (Mann et al ., ) on the development and use of phospho‐site specific antibodies to study homologous and heterologous MOPr regulation, the latter mediated by protein kinase C phosphorylation of MOPr. This could provide an explanation for the protein kinase C (PKC)‐mediated desensitization of MOPr by morphine, when PKC has been activated, as observed in a range of cells (Henderson, ). However, the research paper of Arttamangkul et al .…”
mentioning
confidence: 96%
“…The INRC meeting was opened with the traditional Founders Lecture delivered by Graeme Henderson (Henderson, ). The Founders Lecture honours the contributions of individuals who have a made a sustained and substantial contribution to the science upon which the conference is based.…”
mentioning
confidence: 99%